Effect of simvastatin in hepatic ischemia and reperfusion in rats - Carvalho, Marília Daniela Ferreira; Melo, Laís Izabel Maia; Chacon, Maria Clara Medeiros; Farias, Daniel Costa Rodrigues; Azevedo, Ítalo Medeiros de; Rêgo, Amália Cínthia Meneses; Medeiros, Vítor Brasil; Araújo-Filho, Irami; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2012)
Purpose: Liver injury induced by ischemia and reperfusion is frequently observed in the immediate postoperative period in liver transplantation and partial hepatectomy, when the liver is subjected to a period of partial or total ischemia at various times. The present study aimed to evaluate the effect of simvastatin in preventing liver ischemia-reperfusion injury in rats, using the biodistribution of radiopharmaceuticals, biochemical, immunological and histological analysis. Methods: Eighteen Wistar rats were randomly divided into three equal groups of six each. Group sham; Group IR (isquemia of left and medium hepatic lobes for 45 min; reperfusion for 24 hs); and IR simvastatin group. Animals from IR simvastatin group were treated with simvastatin microemulsion at a dose of 10mg/kg v.o. (gavage) once daily for 5 days before ischemia and reperfusion (IR). Results: Both the right and the left hepatic lobe had higher uptake of fitate-99mTc04 radioactivity in group IR simvastatin than in group IR (p<0.05). The plasma levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactic dehydrogenase (LDH) were measured at the end of each experiment. Simvastatin pretreatment led to a profound decrease in plasma enzyme levels compared with IR rats (p?0.001). Histopathological examination revealed necrotic areas predominantly in the perivenular zone, cytoplasm vacuolization and sinusoidal congestion in an IR group rats. Simvastatin pretreatment strongly protected livers from these changes. Conclusion: In summary, our study provides the evidence that pretreatment with simvastatin protected rat livers from ischemia/reperfusion injury in vivo. This protective effect was validated by a decrease of plasma liver enzymes and histopathological features of liver injury, as well as by biodistribution of fitate-Tc99m in liver tissue.